Optimizing The Use Of Wi-Fi Bandwidth In The Bumi Jaya Village Office Environment - Eka Wahyu Sholeha; Herpendi; Dery Yuswanto Jaya; Dewi Indra Anggraeni (Jurnal Abdimas Cendekiawan Indonesia, 2025)
The efficient management of internet networks in public service environments is critical to supporting productivity and ensuring uninterrupted administrative operations. In Bumi Jaya Village, Pelaihari, Tanah Laut Regency, South Kalimantan, unrestricted use of Wi-Fi particularly for online gaming by local youth had disrupted office activities and compromised service quality. To address this issue, this study implemented the Queue Tree bandwidth management feature on Mikrotik devices, aimed at optimizing network performance and prioritizing essential services. The research was conducted through initial surveys and observations to assess usage patterns and existing infrastructure. A customized Queue Tree configuration was then applied to limit bandwidth for non-essential activities while preserving access. The results demonstrated a substantial improvement in bandwidth efficiency, with administrative and public service tasks receiving consistent and prioritized connectivity. Moreover, the initiative contributed to a more professional work atmosphere, reducing distractions, noise, and improper use of public facilities. Importantly, the program also involved capacity building for village office staff, equipping them with practical knowledge to monitor and manage the network sustainably. This approach not only resolved technical issues but also supported the development of digital governance competencies at the local level. The implementation of Queue Tree proved to be a strategic solution that enhances digital infrastructure, promotes responsible internet use, and fosters a more effective public service environment.